PENGARUH KEPEMILIKAN MANAJERIAL, DEBT CONVENANT DAN RISIKO LITIGASI TERHADAP KONSERVATISME AKUNTANSI - Cindi Furwati; Dirvi Surya Abbas; Hamdani Hamdani; Seleman Hardi Yahawi (Jurnal Ekonomi, Bisnis dan Manajemen, 2022)
The purpose of this research is to examine the effect of Managerial Ownership, Debt Convenant and Litigation Risk on Accounting Conservatism. The population in this study consisted of manufacturing companies, the consumer goods industry sub-sector which were listed on the Indonesia Stock Exchange in 2015-2018. A sample of 12 companies used in this study was found by purposive sampling method. The data used is secondary data. Data analysis was performed with descriptive statistics using panel data regression analysis techniques. The empirical results of this study indicate that independent Debt Convenant does not have a statistically significant effect on Accounting Conservatism while Managerial Ownership and Litigation Risk have a significant negative effect on Accounting Conservatism. The results show that managerial ownership has a significant positive effect on Accounting Conservatism, and Litigation Risk has a significant positive effect on Accounting Conservatism, debt agreements do not have a significant effect on Accounting Conservatism, and managerial ownership, litigation risk together have an effect on Accounting Conservatism.